2009
DOI: 10.4014/jmb.0901.083
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter antiviralis sp. nov., from Tobacco Plant Roots

Abstract: Acinetobacter strain KNF2022 T was isolated from tobacco plant roots during the screening of antiviral substances having inhibitory effects on Tobacco mosaic virus (TMV) and examined by phenotypic, chemotaxonomic, and genetic characterization. It was a nonmotile, Gram-negative bacterium. This strain contained Q-9 as the main respiratory quinone. The major cellular fatty acids of the isolate were 16:0, 18:1 w9c, and 16:1 w7c/15 iso 2OH. The DNA base composition was 44 mol%. Phylogenetic analysis based on the 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Interestingly, a recent study has shown that Acinetobacter sp. strain KNF2022 was able to produce an antiviral compound with inhibitory effects on the tobacco mosaic virus [56]. The role that the cultivable bacteria found here may play in the bio-ecology or vectorial competence of Ae.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, a recent study has shown that Acinetobacter sp. strain KNF2022 was able to produce an antiviral compound with inhibitory effects on the tobacco mosaic virus [56]. The role that the cultivable bacteria found here may play in the bio-ecology or vectorial competence of Ae.…”
Section: Discussionmentioning
confidence: 75%
“…A recent study has shown that an Acinetobacter sp. strain is able to inhibit a tobacco mosaic virus by producing an antiviral compound (Lee et al , 2009). Many other groups of bacteria detected for the first time in mosquitoes perform unknown functions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has shown that Acinetobacter antiviralis sp. nov. from Tobacco plant roots was able to produce an antiviral compound with inhibitory effects on tobacco mosaic virus multiplication (Lee et al . 2009).…”
Section: Discussionmentioning
confidence: 99%